PENERAPAN SISTEM POMPA AIR TENAGA SURYA UNTUK PENYEDIAAN AIR TANAMAN JAGUNG PADA MUSIM KEMARAU DI DESA SOKKOLIA, KECAMATAN BONTOMARANNU, GOWA-SULSEL - Usman Usman; Ahmad Rosyid Idris; Muhammad Ruswandi Djalal; Muhammad Thalib; Mustika Ayu; Muh. Ikhra Aliefka Putramardani (Jurnal Abdi Insani, 2022)
Farmers in the hamlet of Borong Rappo, Sokkolia Village, Bontomarannu District, Gowa Regency with an area of 10 ha of rice fields. In the dry season, water for irrigation is obtained from wells or reservoirs. For water to be channeled to the fields, the water in the well or reservoir is pumped using a pump machine. There are two types of pump machines used by farmers, namely machines with petalite fuel and those using gas, thereby increasing production costs. This activity aims to help farmers reduce operational costs in the form of fuel costs by implementing a Solar photovoltaic water pumping system (SPVWPS). SPVWPS has almost 0 (zero) operational costs. The procedure for implementing this PKM activity begins with a site survey and discussions with partners to determine solutions to problems. The types of SPVWPS implemented are direct driven type and deep well (submersible) pump type. The implemented SPVWPS capacity is 900 Wp for solar panels and 700 W for DC pumps. The results of observations of pump performance in sunny conditions the pump can produce a discharge of 84.1 l/minute so it takes about 2.77 hours to meet the water needs of each paddy field. While in cloudy conditions this SPTAS can pump 53.3 l/minute of water, in this condition it takes 4.38 hours to meet water needs. The SPTAS system can eliminate pump operating costs and the average time needed to meet water needs each day is 3.75 hours.